Codification and Legal Legitimization of Islamic Economic Law in Indonesia’s National Legal System - Sari, Junia; Wira, Ahmad; Hendra, Testru; Salmy Edawati Yaacob (ASAS, 2026)
This study analyzes the codification and legal legitimization of Islamic economics in strengthening the Islamic economic system in Indonesia. This study is motivated by the growing need for legal certainty and formal recognition of the ever-evolving practices of Islamic economics, while research on the contribution of codification and legal legitimization to the strengthening of the Islamic economic system remains limited. The research employs a qualitative method with a normative approach through a literature review of various regulations and related literature. The results of the study indicate that the codification of Islamic economic law has been realized through various national regulations, particularly the Compilation of Islamic Economic Law (KHES) based on Supreme Court Regulation No. 2 of 2008 and Law No. 21 of 2008 on Islamic Banking. These findings indicate that codification not only provides legal certainty but also strengthens institutional legitimacy, supports the resolution of Islamic economic disputes, and fosters the development of the Islamic economic industry. The novelty of this study lies in its analysis of the relationship between codification and legal legitimacy as instruments for strengthening the integration of Islamic law into the national legal system. Theoretically, this study enriches the field of Islamic economic law, while practically, it provides input for regulators in refining regulations to enhance legal certainty and public confidence in the Islamic economy in Indonesia.